Development and evaluation of a specific judo grip-strength-test - Heinisch, H. D.; Knoll, Kl.; Kindler, M.; Haupt, H. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
"The skills of gripping are the key to success". These are the words in which Adams (1990) describes the outstanding function of the Kumi-kata in judo. In this sport, nearly every strength transfer on the opponent is regulated by the hands via the combat clothing. Therefore, the strength to grip or hold the sleeve or lapel is very important to successfully execute fighting actions with throwing techniques, and it has to be differentiated between Tsurite and Hikite (Weers, 1998; Morrell, 2004; 2006). As a consequence of a modified combat control not only coaching practice, but also sport science has been focusing on grip strength during the last few years (Crosby et al., 1994; Lee und Quan; 2004; Franchini et al., 2005; Bonitch-Gondora et al., 2011; Sánchez et al., 2011; Dias et al., 2012). However, most of the studies on combat sports are based on measuring the "hand squeezing strength", e. g. by using the hydraulic hand dynamometer (Schmidt & Toews, 1970). By looking far ahead, Franchini et al. (2011) and da Silva et al. (2012) have decided to measure grip and hold strength on the sleeve of the kimono. Our measuring system is to measure the grip strength performance at the sleeve, too, and at the lapel of a judo jacket, without allowing the influence of other muscle groups. One of the first goals is to examine the reliability of the test. Procedure: The test person`s upper arm is fixed and he grabs a tightened judo sleeve or lapel by sleeve or lapel grip. The grip devices are pulled continuously in horizontal direction by a tension spindle, which is operated by an electric motor. A power sensor between the tension spindle and the sleeve/lapel measures the effective power. Via a measurement box with a registration frequency of 100 Hz (quasi static measurement procedure) the amplified measurement signal is transmitted to a PC. In April 2013, the first tests with 5 national men`s teams will be carried out. Then, test retest reliability studies are of immediate importance for maximum grip strength of the right and the left sleeve of lapel grip. Results: The results will be discussed according to dependence of grip/hold strength on body weight, grip position, type of grip (sleeve, lapel), and hand dominance.